Effects of dietary cholesterol and fatty acids on plasma lipoproteins. - Schonfeld, G (1982)
The effects of dietary cholesterol and fatty acids on low density and high density lipoproteins (LDL and HDL) were studied in 20 young men. After 2-3 wk of evaluations on ad lib. diets, basal diets, which consisted of 15% protein, 45% carbohydrates, 40% fat, and 300 mg/day of cholesterol, were given for 4-5 wk (Basal). The ratio of dietary polyunsaturated to saturated fatty acids (P/S) for different groups of subjects were 0.25, 0.4, 0.8, or 2.5. 750 and 1,500 mg/d of cholesterol were added to the basal diets as 3 and 6 eggs, respectively. Total cholesterol and LDL cholesterol were lower in all subjects on the basal diets than on the ad lib. diets. Addition of 750 mg cholesterol to the diet with P/S = 0.25-0.4 raised LDL cholesterol by 16 +/- 14 mg/dl to 115% of basal diet values (n = 11, P less than 0.01); 1,500 mg increased LDL cholesterol by 25 +/- 19 mg/dl to 125% (n = 9, P less than 0.01). On the diet with P/S = 0.8, 750 mg produced insignificant increases in LDL cholesterol, but 1,500 mg produced increases of 17 +/- 22 mg/dl to 115% of basal (n = 6, P less than 0.02). On the P/S = 2.5 diet, neither 750 nor 1,500 mg produced significant changes. Thus, both the cholesterol contents and P/S ratios of diets were important in determining LDL levels. The lipid and apoprotein compositions, flotation rates, molecular weights, and binding by cellular receptors of LDL were virtually unchanged by the addition of cholesterol to the diets high in saturated fat. These diets, therefore, caused an increase in the number of LDL particles of virtually unchanged physical and biological properties. On the diet with low P/S ratio, HDL2 rose, whereas this effect was absent on diets with high P/S ratios. The response of LDL to dietary manipulations is consonant with epidemiologic data relating diets high in cholesterol and saturated fat to atherogenesis. The response of HDL2, however, is opposite to that of its putative role as a negative risk factor. Further work is needed to clarify this interesting paradox.